42.9k views
4 votes
Consider the explicit formulas for two sequence ​

2 Answers

6 votes

Answer:

The one above is right.

Explanation:

User Skysign
by
5.2k points
3 votes

These are the formulas right?.. I hope so, anyways..

- f(n)= 2^(n-1) -1

- g(n)=3n+6

f(7)=2^{7-1}-1 - f(7)=2^{6}-1 - f(7)=64-1 - f(7) = 63

g(10)=3\X 10+6 - g(10)=30+6 - g(10) = 36

= f(7)>g(10)

I hope that it helped..

User XjeaxaxX
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.